Age Differences in Multimodal Quantitative Sensory Testing and Associations With Brain Volume. Issue 3 (22nd August 2021) - Johnson, Alisa J; Wilson, Abigail T; Laffitte Nodarse, Chavier; Montesino-Goicolea, Soamy; Valdes-Hernandez, Pedro A; Somerville, Jessie; Peraza, Julio A; Fillingim, Roger B; Bialosky, Joel; Cruz-Almeida, Yenisel
Abstract: Background and Objectives: Somatosensory function is critical for successful aging. Prior studies have shown declines in somatosensory function with age; however, this may be affected by testing site, modality, and biobehavioral factors. While somatosensory function declines are associated with peripheral nervous system degradation, little is known regarding correlates with the central nervous system and brain structure in particular. The objectives of this study were to examine age-related declines in somatosensory function using innocuous and noxious stimuli, across 2 anatomical testing sites, with considerations for affect and cognitive function, and associations between somatosensory function and brain structure in older adults. Research Design and Methods: A cross-sectional analysis included 84 "younger" ( n = 22, age range: 19–24 years) and "older" ( n = 62, age range: 60–94 years) healthy adults who participated in the Neuromodulatory Examination of Pain and Mobility Across the Lifespan study. Participants were assessed on measures of somatosensory function (quantitative sensory testing), at 2 sites (metatarsal and thenar) using standardized procedures, and completed cognitive and psychological function measures and structural magnetic resonance imaging. Results: Significant age × test site interaction effects were observed for warmth detection ( p = .018, η p 2 = 0.10) and heat pain thresholds ( p = .014, η p 2 = 0.12). Main age effects were observed for mechanical, vibratory, cold, and warmth detection thresholds ( p s < .05), with older adults displaying a loss of sensory function. Significant associations between somatosensory function and brain gray matter structure emerged in the right occipital region, the right temporal region, and the left pericallosum. Discussion and Implications: Our findings indicate healthy older adults display alterations in sensory responses to innocuous and noxious stimuli compared to younger adults and, furthermore, these alterations are uniquely affected by anatomical site. These findings suggest a nonuniform decline in somatosensation in older adults, which may represent peripheral and central nervous system alterations part of aging processes.